Scalp cooling as a strategy to reduce alopecia induced by cancer chemotherapy: systematic review (Research, Society and Development, 2021)
Objective: To analyze the available evidence on the use of the scalp cooling technique in reducing alopecia in cancer patients undergoing chemotherapy and its repercussions for nursing care. Method: Systematic review based on PRISMA checklist recommendations, without date restrictions, in the following databases: Pubmed, Cinahal, Cochrane and Scopus. Results: Of 579 published articles, 10 were included published between 2015 and 2020. Patients who used the therapy were more successful in terms of capillary preservation, ranging from 45.6% response with grade 3 assessment of alopecia, to 89% with rate greater than 50% of alopecia using taxanes. It is important to emphasize that there are cases of failure or partial fall and the factors that can influence this result. Conclusion: The effectiveness of the technique and the importance of nursing in this process were evidenced in order to provide a better quality of life and treatment for these patients.